Preferential host switching and its relation with Hantavirus diversification in South America - Rivera, Paula Cecilia (2015)
In recent years, the notion of co-speciation between Hantavirus species and their hosts was discarded in favour of a more likely explanation: preferential host switching. However, the relative importance of this last process in shaping the evolutionary history of hantaviruses remains uncertain, given the present limited knowledge not only of virus–host relationships but also of the pathogen and reservoir phylogenies. In South America, more than 25 hantavirus genotypes were detected; several of them act as aetiological agents of hantavirus pulmonary syndrome (HPS). An understanding of the diversity of hantaviruses and of the processes underlying host switching is critical since human cases of HPS are almost exclusively the result of human–host interactions. In this study, we tested if preferential host switching is the main process driving hantavirus diversification in South America, by performing a co-phylogenetic analysis of the viruses and their primary hosts. We also suggest a new level of amino acid divergence to define virus species in the group. Our results indicate that preferential host switching would not be the main process driving virus diversification. The historical geographical proximity among rodent hosts emerges as an alternative hypothesis to be tested.